1998
DOI: 10.1111/j.1432-2277.1998.tb01134.x
|View full text |Cite
|
Sign up to set email alerts
|

Experience with Neoral versus Sandimmune in primary liver transplant recipients

Abstract: We compared results using Neoral versus Sandimmune, each in combination with steroid and azathioprine immunosuppression, in primary liver transplantation recipients. There were 15 patients in each group with similar demographic distributions. Intravenous cyclosporine was stopped at 4.3 +/- 1.9 days in the Neoral group vs 7.8 +/- 4.9 days in the Sandimmune group. (P < 0.025). Cyclosporine levels in the first 10 days were higher (mean 306 ng/ml vs 231 ng/ml) in the Neoral group than the Sandimmune group (P < 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In human transplant patients, the use of microemulsified cyclosporine reduced the number of rejection episodes compared with the oil‐based formulation in renal allografts (35% v 50% to 60%) and liver transplants (24% v . 70%) 47,48 . In dogs, the pharmacokinetics of oil‐based cyclosporine and efficacy of this formulation to prevent renal allograft rejection have been reported, 8,9,12,49 but to the authors' knowledge, there are no similar reports on microemulsified cyclosporine.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In human transplant patients, the use of microemulsified cyclosporine reduced the number of rejection episodes compared with the oil‐based formulation in renal allografts (35% v 50% to 60%) and liver transplants (24% v . 70%) 47,48 . In dogs, the pharmacokinetics of oil‐based cyclosporine and efficacy of this formulation to prevent renal allograft rejection have been reported, 8,9,12,49 but to the authors' knowledge, there are no similar reports on microemulsified cyclosporine.…”
Section: Discussionmentioning
confidence: 98%
“…46 In human transplant patients, the use of microemulsified cyclosporine reduced the number of rejection episodes compared with the oil-based formulation in renal allografts (35% v 50% to 60%) and liver transplants (24% v. 70%). 47,48 In dogs, the pharmacokinetics of oil-based cyclosporine and efficacy of this formulation to prevent renal allograft rejection have been reported, 8,9,12,49 but to the authors' knowledge, there are no similar reports on microemulsified cyclosporine. The improved intestinal absorption and increased bioavailability of microemulsified cyclosporine may ex-plain the improved renal allograft survival in mismatched dogs observed in this study compared with previous reports using oil-based cyclosporine.…”
Section: Discussionmentioning
confidence: 98%
“…In particular, younger children and children with Roux-en-Y biliary anastomosis or cholestasis showed more consistent drug absorption with Neoral (48-50). Studies using Neoral have shown a reduced incidence of rejection as compared with Sandimmune in liver recipients, with no significant difference in toxicity (51)(52)(53).…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…27 Studies using Neoral have shown a reduced incidence of rejection as compared with Sandimmune CsA in liver recipients, with no significant difference in toxicity. [28][29][30] Recent pharmokinetic studies of Neoral have shown that the absorption phase (0-4 hrs) has the greatest individual variability. Furthermore, the blood concentration of cyclosporin 2 hours after oral ingestion (C 2 ) correlated better with AUC than the commonly measured trough concentration (C 0 ).…”
Section: Cyclosporin Amentioning
confidence: 99%